The Political Economy of EU Enlargement: Or, Why Japan is not a Candidate Country? - Antonis Adam; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2002)
In this paper we argue that strong political economy forces explain the rush of the EU to expand eastwards. We use a model of vertical product differentiation in order to claim that technologically- advanced EU firms (residing in high-income member countries) prefer a mutual market-opening with less technologically sophisticated countries than multilateral liberalization, which would necessarily involve the reciprocal opening of markets with other technologically-advanced countries. By the same token, less technologically sophisticated firms residing in low-income member countries would prefer an enlargement that is directed towards high-income countries. The evidence presented in the paper supports our hypothesis.
Keywords: 330; EU enlargement; vertically differentiated products; political economy; customs unions